2020
DOI: 10.3389/fcimb.2020.00106
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bacterial Vaginosis Is Associated With Depletion of Mature Superficial Cells Shed From the Vaginal Epithelium

Abstract: Previous studies have described bacterial vaginosis (BV) as associated with increased cell-shedding from the cervicovaginal epithelium. Cell-shedding in excess of cell-proliferation is thought to decrease epithelial barrier function and increase susceptibility to infection. This study evaluated the number of shed cells in mid-vaginal smears from women with a diagnosis of symptomatic BV (sBV, n = 17), asymptomatic BV (aBV, n = 71), or no BV (n = 104) by Amsel criteria. The sBV smears contained significantly mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
(56 reference statements)
1
13
0
Order By: Relevance
“…With no risk of antimicrobial resistance, the use of probiotic lactobacilli as a prophylaxis for symptomatic BV appears coherent. Asymptomatic BV is also highly prevalent in women, associated with a lactobacilli-deficient condition [ 6 , 25 ] and an increased risk of infection due to disruption of the vaginal epithelium [ 26 ]. However, it is largely unknown whether the lactobacilli present during eubiosis have different functional properties than lactobacilli during asymptomatic BV.…”
Section: Discussionmentioning
confidence: 99%
“…With no risk of antimicrobial resistance, the use of probiotic lactobacilli as a prophylaxis for symptomatic BV appears coherent. Asymptomatic BV is also highly prevalent in women, associated with a lactobacilli-deficient condition [ 6 , 25 ] and an increased risk of infection due to disruption of the vaginal epithelium [ 26 ]. However, it is largely unknown whether the lactobacilli present during eubiosis have different functional properties than lactobacilli during asymptomatic BV.…”
Section: Discussionmentioning
confidence: 99%
“…The low ZO-1 proteins in the cervico-vaginal lavages of HIV-negative pregnant women with a diverse vaginal microbiota i.e. CT3 and CT4 could possibly be due to the decreased cell proliferation and differentiation as has been previously reported 30 . Women with a non-Lactobacillus dominant vaginal microbiota have a higher number of immature epithelial cells 31 which have lower expression of tight junction proteins.…”
Section: Discussionmentioning
confidence: 54%
“…Fibroids were a common finding on TVUS; however, there are no data relating fibroids to the vaginal epithelium. The vaginal microbiota was not evaluated, and we have previously shown that asymptomatic bacterial vaginosis (BV) is associated with the shedding of fewer, lower MI epithelial cells [15]. While menses did not appear to significantly influence our analysis and there was no association between hormonal contraception and baseline MI, we were unable to model menstrual cycle phase or specific types of hormonal contraception due to sample size limitations.…”
Section: Plos Onementioning
confidence: 96%
“…Lactic acid is a broad-spectrum bactericide and viricide [8][9][10][11], and also has a significant anti-inflammatory effect on the VE [12,13]. Detachment/shedding of the outer layer of mature cells in excess of proliferation/maturation rates will expose the underlying living cells [Fig 1C], and it has been hypothesized that this may influence susceptibility or resistence to reproductive tract infections [14,15]. The spermicide N9 causes an increase in detachment/shedding of epithelial cells that is associated with increased risk of HIV infection [16].…”
Section: Introductionmentioning
confidence: 99%